The Transcendental properties of being - Elders, Leo (Sapientia, 2003)
In metaphysics the term «transcendental» is used to denote the different aspects of being, that is of whatever is real. The term indicates that being and its properties are present in each of the predicaments or categories, such as substance, quantity, quality, relation, location, time, action, etc. Therefore, they «transcend» the limits of these different classesl. Some early Greek philosophers had noticed that whatever exists must have some unity and goodness, but they never treated the theme systematically. The philosophy of being begins with Parmenides who describes his fulgurant intuition of the unitary and unchangeable character of being as having been revealed to him from aboye. Being is and not-being is not. Being is one and immutable; it is also knowable, for being and thinking, he writes, are the same. A century later Plato intimates that the highest reality, the Good, is beautiful and is one. However, he did not say that all existent things are good and beautiful...